Screening for asymptomatic mpox in at-risk populations: A cross-sectional study - Inés Armenteros-Yeguas; Reynaldo Homen; Adrián Valls; Laura Dans; Eva Orviz; Oskar Ayerdi; Teresa Puerta; Mar Vera; Jorge Alfredo Pérez-García; Montserrat Torres; Mayte Coiras; Jorge Del Romero; et al. (PLoS ONE, 2025)
Background Mpox is a viral disease caused by an orthopoxvirus called monkeypox virus. It experienced a significant increase in cases in 2022 worldwide, mostly with sexual transmission. The possibility of hidden circulation of this infection among asymptomatic individuals remains unclear. Methods This is a multi-centre, observational cross-sectional study conducted in a sexually transmitted infections (STIs) clinic in its referral hospital between July and October 2023 in Madrid, Spain. Pharyngeal and rectal swab samples were collected from each participant and processed to detect bacterial STIs and mpox. Socio-demographic, clinical and behavioural data were collected, and a descriptive analysis was performed. Results A total of 343 asymptomatic participants were included. The prevalence of asymptomatic mpox infection was 0.3% (n = 1) and the only positive case developed symptoms shortly after sampling, ruling out a fully asymptomatic infection. The percentage of vaccinated individuals was 36.1%. 13.2% had previously contracted mpox. Other STIs were detected in 21.6% of participants. Conclusions Although routine screening for asymptomatic bacterial sexually transmitted infections is strongly recommended in at-risk individuals, testing for asymptomatic mpox should be evaluated based on the specific context and population. Additionally, the ongoing cases of mpox in Spain are likely not related to the presence of asymptomatic carriers.